Difference between revisions of "1993 USAMO Problems/Problem 5"
(→Solution) |
|||
Line 30: | Line 30: | ||
<cmath>a_{n-3} a_{n-1} \le a_{n-2}^2</cmath> | <cmath>a_{n-3} a_{n-1} \le a_{n-2}^2</cmath> | ||
<cmath>a_{n-2} a_n \le a_{n-1}^2.</cmath> | <cmath>a_{n-2} a_n \le a_{n-1}^2.</cmath> | ||
− | Multiply all inequalities together and cancel <math>a_1, a_2^2, a_3^2, \dots, a_{n-2}^2, a_{n-1}</math> to give <math>a_0 a_n \ | + | Multiply all inequalities together and cancel <math>a_1, a_2^2, a_3^2, \dots, a_{n-2}^2, a_{n-1}</math> to give <math>a_0 a_n \le a_1 a_{n-1}</math>. Similarly, by multiplying all inequalities except the first and the last, we deduce that <math>a_2 a_{n-2} \le a_1 a_{n-1} \ge a_0 a_n</math>, and a simple induction argument proves the verity of the Fact for <math>1 \le i \le \frac{n}{2}</math>, and so by the Commutative Property the Fact is true for all <math>1 \le i \le n-1</math>, as desired. Now multiply each inequality of the Fact for <math>i = 1, 2, 3, \dots, n-1</math> to give the desired result. |
Note: The Fact can be generalized into a Lemma: <math>a_x a_w \le a_y a_z</math> whenever <math>x \le y \le z \le w</math> and <math>x + w = y + z</math>. The proof is similar to that of the Fact and is left as an exercise to the reader. | Note: The Fact can be generalized into a Lemma: <math>a_x a_w \le a_y a_z</math> whenever <math>x \le y \le z \le w</math> and <math>x + w = y + z</math>. The proof is similar to that of the Fact and is left as an exercise to the reader. |
Latest revision as of 18:08, 1 June 2020
Problem 5
Let be a sequence of positive real numbers satisfying for . (Such a sequence is said to be log concave.) Show that for each ,
Solution
Notice that because we may subtract from both sides of the inequality and observe that it is sufficient to prove that or
Fortunately, this is an easy inequality. Indeed, from AM-GM applied on each group of terms we have and so it suffices to prove or, after taking both sides to the power, simplifying, and taking the -th root of both sides, to prove This easily follows from the Fact that for . Indeed, we are given that Multiply all inequalities together and cancel to give . Similarly, by multiplying all inequalities except the first and the last, we deduce that , and a simple induction argument proves the verity of the Fact for , and so by the Commutative Property the Fact is true for all , as desired. Now multiply each inequality of the Fact for to give the desired result.
Note: The Fact can be generalized into a Lemma: whenever and . The proof is similar to that of the Fact and is left as an exercise to the reader.
--User suli, April 15, 2015.
See Also
1993 USAMO (Problems • Resources) | ||
Preceded by Problem 4 |
Followed by Last Problem | |
1 • 2 • 3 • 4 • 5 | ||
All USAMO Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.